Shaping the Canons of Ancient Greek Historiography - Matijašić, Ivan (De Gruyter, 2018)
The main focus of this book is the ancient formation and development of the canons of Greek historiography. It takes a fresh look on the modern debate on canonical literature and deals with Greek historiographical traditions in the works of ancient rhetors and literary critics. Writings on historiography by Cicero, Quintilian, and Dionysius of Halicarnassus are chiefly taken into account to explore the canons of Greek historians in Hellenistic and Roman Imperial Ages. Essential in canon-formation was the concept of classicism which took shape in the Age of Augustus, but whose earlier developments can be traced back to Isocrates, a model rhetor according to Dionysius at the end of the 1st century BC. The analysis explores also late-antique authors of school treatises and progymnasmata, a field where historiography had a pedagogical function. Previous studies on canonical literature have rarely considered historiography. This book examines not only the works of ancient historians and their legacy, but also the relationship between historiography, literary criticism, and the rhetorical tradition
10.1515/9783110476279
Keywords: Historians / Greece; Ancient historiography; Geschichtsschreibung; Klassizismus; Rhetorik; canonical literature; classicism; literarischer Kanon; rhetorical treatises; LITERARY CRITICISM / Ancient & Classical